Trusting the gold : uncovering your natural goodness - Brach, Tara (Sounds True, 2021)
"Trusting the Gold is a beautiful gem of a gift book featuring stories, teachings, and reflection prompts for readers, along with approximately 30 gorgeous illustrations by Vicky Alvarez. The book is divided into three themes--wisdom, compassion, and freedom (awareness) and is meant to serve as a balm for readers, reminding us that even when we seem to have lost sight of the gold in ourselves, the light of our true nature cannot be dimmed, tarnished, or erased. No matter how many layers of doubt and fear cover our basic goodness, it is always there, waiting to be discovered and to shine through in all parts of our life"--